Niger - Public Expenditure Tracking Survey : Education and Health - Survey Questionnaire - World Bank (World Bank, 2012)
The objective of the first Public Expenditure Tracking Survey (PETS) for Niger is to increase understanding of the link between public spending and service delivery at the facility level in order to contribute to improving the effectiveness and accountability in the use of public funds. Specifically, this PETS focuses on identifying the discrepancies, inefficiencies and delays in public spending execution for selected expenditures in the education and health sectors. The medium to long term goal of these PETS is to launch a process aimed at continuous improvements in public expenditure efficiency and equity by focusing on capacity building in this area in the ministries of education and health and in the Institute of National Statistics (INS). The main challenge faced by a tracking survey in a country like Niger is the availability and accuracy of records keeping. The Niger PETS highlights a general lack of systematic information recording. The quality of records in the education sector is low and data often incomplete. This is especially a problem when a higher level agency distributes resources to lower level agencies. The absence of downstream records indicates a lack of systems for downward accountability and can facilitate the diversion of resources. This compares unfavorably with a country such as Ghana, where the quality of record is good between the central agency and district offices.